2010
DOI: 10.1111/j.1743-6109.2009.01562.x
|View full text |Cite
|
Sign up to set email alerts
|

Independent Determinants of Coronary Artery Disease in Erectile Dysfunction Patients

Abstract: Introduction There is growing evidence of a link between erectile dysfunction (ED) and coronary artery disease (CAD). Aims The purpose of this study was to explore the independent determinants of CAD in ED outpatients. Methods This study enrolled 243 patients, ranging in age from 21 to 81 years old, suffering from ED as diagnosed by the International Index of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 49 publications
1
15
0
Order By: Relevance
“…Actually, the pathophysiology of the endothelial function and the relationship between cardiovascular events and ED are not fully understood so far. Previous studies showed that ED is predictive of subsequent atherosclerotic cardiovascular events [31][32][33][34]. This study suggests that ED may be a marker for endothelial dysfunction, even in patients without clinical evidence of atherosclerosis.…”
Section: Discussionsupporting
confidence: 63%
“…Actually, the pathophysiology of the endothelial function and the relationship between cardiovascular events and ED are not fully understood so far. Previous studies showed that ED is predictive of subsequent atherosclerotic cardiovascular events [31][32][33][34]. This study suggests that ED may be a marker for endothelial dysfunction, even in patients without clinical evidence of atherosclerosis.…”
Section: Discussionsupporting
confidence: 63%
“…Our previous study results also showed independent determinants, including many traditional cardiovascular risk factors and markers of vascular wall and ventricular function, of CAD in ED outpatients. 6 In addition, metabolic syndrome (MS), which refers to the clustering of criteria such as DM or impaired glucose tolerance, hypertension, obesity, dyslipidemia and/or microabluminuria, is closely associated with cardiovascular morbidity and mortality. 7,8 The relationship of ED and MS had been well established by several studies.…”
Section: Introductionmentioning
confidence: 99%
“…IR was defined as QUICKI <0.357 derived from Hrebicek's population‐based study [20]. High level of glycosylated serum protein (GSP) [16] and hs‐CRP [21,22], which had been considered to be associated with CVD, were screened as risk factors for ED. The diagnostic criteria of these biochemical indicators, derived from National Clinical Testing Criterion, were defined as GSP >236 mg/L and hs‐CRP >3.00 mg/L, respectively.…”
Section: Participants and Methodsmentioning
confidence: 99%